Member selection criteria in fruit and vegetable producer organizations in Poland - Chlebicka, Aleksandra; Pietrzak, Michał (Turystyka i Rozwój Regionalny, 2023)
The role of producer organizations (POs) in enhancing the efficiency of agricultural production and empowering farmers within the agro-food supply chain has gained significant attention among scholars and policymakers. These organizations play a crucial role in addressing the challenges faced by farmers, such as market volatility, limited access to resources, and unequal bargaining power. The primary objective of this paper is to delve into the selection criteria employed by POs and classify them accordingly. By doing so, we aim to gain a deeper understanding of how the member selection process evolves over time and to highlight any divergences between POs that are actively operating and those that have ceased their operations. By contrasting the selection processes of active POs with those that have discontinued their operations, we hope to uncover potential reasons for the success of these entities. To accomplish this, our study focuses on a sample of 70 producer organizations composed of fruit and vegetable growers situated in two voivodships in Poland.